2019
DOI: 10.1186/s12931-019-1015-0
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin-sensitized mice have altered airway inflammation to agriculture organic dust

Abstract: Agriculture exposures are associated with reducing the risk of allergy and asthma in early life; yet, repeated exposures later in life are associated with chronic bronchitis and obstructive pulmonary diseases. The objective of this study was to investigate the airway inflammatory response to organic dust extract (ODE) in mice with established ovalbumin (OVA)-induced experimental asthma. C57BL/6 mice were either OVA sensitized/aerosol-exposed or saline (Sal) sensitized/aerosol-challenged. Both groups were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
2
16
0
1
Order By: Relevance
“…In the study by Van Maele et al, ROR γ t + ILC3s account for 30% of the total ILCs in the murine lungs, most of which coexpress C-C motif chemokine receptor 6 (CCR6, the receptor for the epithelial chemokine CCL20) ( Van Maele et al, 2014 ). There are approximately 2,000 to 22,000 pulmonary ILC3s in the wide-type mice in various studies ( Kim et al, 2014 ; Van Maele et al, 2014 ; Everaere et al, 2016 ; Yanagisawa et al, 2017 ); however, the number reported by Ardain et al is far smaller than the other studies in the Mycobacterium tuberculosis (Mtb)-infected murine lungs ( Ardain et al, 2019 ) and in the murine bronchoalveolar lavage fluid (BALF) ( Warren et al, 2019 ). There might be many reasons for the discrepancies, for example, biology and characterization differences of ILC3s within the lungs and airways between species, and not exactly the same cell populations defined in various studies with diverse markers.…”
Section: Group 3 Innate Lymphoid Cellsmentioning
confidence: 99%
“…In the study by Van Maele et al, ROR γ t + ILC3s account for 30% of the total ILCs in the murine lungs, most of which coexpress C-C motif chemokine receptor 6 (CCR6, the receptor for the epithelial chemokine CCL20) ( Van Maele et al, 2014 ). There are approximately 2,000 to 22,000 pulmonary ILC3s in the wide-type mice in various studies ( Kim et al, 2014 ; Van Maele et al, 2014 ; Everaere et al, 2016 ; Yanagisawa et al, 2017 ); however, the number reported by Ardain et al is far smaller than the other studies in the Mycobacterium tuberculosis (Mtb)-infected murine lungs ( Ardain et al, 2019 ) and in the murine bronchoalveolar lavage fluid (BALF) ( Warren et al, 2019 ). There might be many reasons for the discrepancies, for example, biology and characterization differences of ILC3s within the lungs and airways between species, and not exactly the same cell populations defined in various studies with diverse markers.…”
Section: Group 3 Innate Lymphoid Cellsmentioning
confidence: 99%
“…Ovalbumin sensitization and challenge were performed following a sensitization protocol with chicken OVA and alum as described previously [23,[26][27][28][29][30]. C57BL/6 wild-type and TRPV4 KO mice were sensitized with an allergen by intraperitoneal injection of 100 μl PBS containing 100 μg OVA and 4 mg aluminum hydroxide (Imject Alum Adjuvant, Thermo Fisher Scientific, Waltham, MA) on day zero.…”
Section: Ovalbumin Sensitization and Challengementioning
confidence: 99%
“…Mouse models of asthmatic inflammation using chicken OVA as an allergen have been well characterized [23,[26][27][28][29][30]. Following intraperitoneal injection of OVA mixed with alum and subsequent challenge with OVA, allergic inflammation develops, which is characterized by BAL and lung tissue eosinophilia, airway remodeling, induction of Th2 cytokines, and AHR.…”
Section: Trpv4 Is Not Involved In the Development Of Airway Hyperrespmentioning
confidence: 99%
“…Similarly, a very recent study demonstrated that PM2.5 disturbs the balance of Th17/Treg cells by impairing differentiation of T reg cells and promoting differentiation of Th17 cells through the molecular pathways AhR–HIF-1α (hypoxia-inducible factor-1alpha) and AhR–Got1 (glutamate oxaloacetate transaminase 1) in a cockroach allergen-induced mouse model of asthma (31). Warren et al reported that acute inhalant exposure to an agriculture acquired organic dust extract (ODE) impacts lung inflammatory responses in a murine model of experimental allergic asthma, suggesting that allergic asthma may prime the lung microenvironment response toward an exaggerated response following exposure to a dusty farm environment (32). Thus, future studies are warranted to identify the underlying mechanisms regarding the co-exposure-induced exacerbation of allergic asthma.…”
Section: Introductionmentioning
confidence: 99%